EVALUASI KEAMANAN WIRELESS LAN MENGGUNAKAN ISSAF (INFORMATION SYSTEM SECURITY ASSESSMENT FRAMEWORK) - Afrizal Zein (Institut Sains dan Teknologi Nasional, 2022)
Abstract The growth of COVID-19 cases continues to increase sharply. In fact, in recent days there has been an increase in cases almost doubled from the previous day. As of March 29, 2020, as stated by the Government spokesperson for handling COVID-19, Achmad Yurianto, has reached 1286 cases, 114 died, 64 recovered. The death rate is 114 cases, which is the highest mortality rate in Southeast Asia. This study tried to predict the spread of covid-19 using Richard's Curve model from early March to the end of June 2020. The results obtained from this study peaked the spread in early May and subsided at the end of June with the results of a prediction of 15 thousand infected people. Keywords: Security Evaluation; ISSAF, Wireless, LAN